WAYS TO DEVELOP ENTREPRENEURSHIP IN THE SERVICE SECTOR (International journal of artificial intelligence, 2025)
The article analyzes the socio-economic significance of the introduction of green technologies in the development of entrepreneurship in the service sector, current shortcomings and future opportunities. The strategy of our country's transition to a green economy, the principles of gender equality and mechanisms for stimulating ecological innovation activities are highlighted.